RIMBA SINKRETIS: The Intersection of Islamic Spirituality in the Local Beliefs of the Indigenous Peoples of Makekal Hulu in Merangin District, Jambi Province - Supian, Supian; Muspawi, Mohammad (Journal of Contemporary Islam and Muslim Societies, 2022)
Abstract: Rimba sinkretis is a set of teachings and beliefs in the Jambi indigenous community, which shows a mixture of elements or understandings with other religions (Islam), which is revealed to be a belief. The ethnographic approach is known to be suitable for elemental and cultural studies. This study reveals three crucial topics: First, there isa meeting point of local religion with Islam which is believed to have been mixed since the syncretic decades through the common teachings and beliefs of one god (monotheism). Second, the meeting point of beliefs that have spiritual similarities to Islam, both in religious expressions and prayers to God, includes Lâ Ilâha Illallâh, Muhammad Rasûlullah, Bismillâh, Salamikum, Allâh Akbar, and Yâ Allâh, so that it does not conflict with their teachings as Muslims. Third, the beliefs of the Orang Rimba community in an almighty God named Allah Ta‘ala, the two prophets named Adam and Muhammad, malakat orang meru as the unseen (spirits), bilik (heaven) and nereko (hell) as places of torment for doso (sin) and pahalo (goodness), baheulo (gods) as jinn and demons, balik ke henteu as the afterlife, Halam Robah as the day of judgment and the orang bek kebudi as good and pious people (ulama). Keywords: Rimba Sinkretis, intersection of Islamic spirituality, local religion, indigenous people